Microbial Biocontainment Systems for Clinical, Agricultural, and Industrial Applications - Pantoja Angles, Aaron; Valle-Pérez, Alexander U.; Hauser, Charlotte; Mahfouz, Magdy M. (Frontiers in Bioengineering and Biotechnology, 2022)
Many applications of synthetic biology require biological systems in engineered microbes to be delivered into diverse environments, such as for in situ bioremediation, biosensing, and applications in medicine and agriculture. To avoid harming the target system (whether that is a farm field or the human gut), such applications require microbial biocontainment systems (MBSs) that inhibit the proliferation of engineered microbes. In the past decade, diverse molecular strategies have been implemented to develop MBSs that tightly control the proliferation of engineered microbes; this has enabled medical, industrial, and agricultural applications in which biological processes can be executed in situ. The customization of MBSs also facilitate the integration of sensing modules for which different compounds can be produced and delivered upon changes in environmental conditions. These achievements have accelerated the generation of novel microbial systems capable of responding to external stimuli with limited interference from the environment. In this review, we provide an overview of the current approaches used for MBSs, with a specific focus on applications that have an immediate impact on multiple fields.